(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2013)
Oil palm empty fruit bunch (OPEFB) was used for the production of Î²-glucosidase by Ganoderma lucidum in submerged fermentation. The activity of Î²-glucosidase had shown an improvement by going from pH 4 to 6 and declined towards alkaline pH. The highest activity (47.75 U/mL) was obtained at pH 6 with 2.0 mm size of substrateâ€™s particle. The smaller the particles size, the higher surface area of substrate which provides more space for hyphae to colonize. Optimum substrate concentration was obtained at 6.0 g/L (43.99 U/mL). The highest Î²-glucosidase activity occurred at 27 ÂºC (53.37 U/mL). The nutrient content in composted OPEFB provides a relevant reason that should be considered in the performance of high activity Î²-glucosidase enzyme. Therefore, the results of this study can be used to produce high activity Î²-glucosidase using cheap and economical substrate (compost OPEFB).